Risk of the contralateral mucosa in patients with oral potentially malignant disorders - Siar, C.H.; Mah, M.C.; Gill, P.P. (2011)
Background: It is known that abnormal changes may occur in any part of the oral mucous membrane exposed to a carcinogen. Therefore patients with oral potentially malignant disorders (PMDs) are at risk of developing similar lesions at multiple sites. Objectives: To determine the risk of the contralateral mucosa in patients presenting with oral PMDs. Materials and methods: Sixty individuals with PMDs were selected for this study. These comprised 32 (53.3) Indians, 23 (38.3) Chinese, four (6.7) Malays and one (1.7) Nepalese. All selected cases had histopathological confirmation of their primary existing lesion as inclusion criteria. Cases that subsequently presented with a lesion in the corresponding anatomical site also underwent scalpel incisional biopsy on this second lesion to verify its diagnosis. The remaining cases that presented with unilateral PMDs at the time of study were subjected to a cytobrush biopsy on the normal looking contralateral mucosa. Results: A total of 70 primary PMDs were detected in 60 patients. The most common PMD found was oral lichen planus (n=40, 57.1). Of the 60 patients studied, 28 (46.6) exhibited bilateral lesions either synchronously (n=21, 35.0) or metachronously (n=7, 11.6). The remaining cases that had undergone cytobrush biopsy on the corresponding anatomical site yielded normal cytological results. Conclusions: Present findings demonstrated that patients presenting with PMDs in the upper aerodigestive tract are at a greater risk of developing a second lesion most probably in the contralateral anatomical site.